MARITIME PIRACY AND ITS EFFECT ON PHYSICAL DISTRIBUTION OF GOODS IN COASTAL COMMUNITIES IN DELTA STATE OF NIGERIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Maritime piracy and consequent armed robbery on the water ways are one of the major contemporary challenges of the river line communities in Nigeria particularly the Niger Delta Region. This phenomenon has a tremendous impact on physical distribution of goods and services and the security of the waterways. The study therefore investigated the effect of maritime piracy on physical distribution of goods in coastal communities in Delta State. Relevant literatures were reviewed. The study adopted survey research design. The inhabitants of Delta State who are involved in the movement of goods along the inland water ways constitute the population of the study. Hundred (100) respondents were purposively selected for the study. Structured questionnaire was employed to generate data from the respondents. Regression analysis was employed in analyzing the data. The study found that maritime piracy has significant negative effect on physical distribution of goods in coastal communities in Delta State. This implies that the activities of pirate along the water ways in Delta state have hampered the free flow of goods in the area. The study contends that the long term solution to the problem of piracy is through the creation of economic opportunities so that the youth could be meaningfully employed. Also security activities should be increased on the water ways and at the sea port to curtail the criminal activities of the pirates.